Integrated Curriculum and Instruction based on Local Wisdom in Sekolah Alam Bengawan Solo (SABS): An Innovation in the Implementation of Character Education - Yuli Ardika Prihatama; Suyudi Suyudi; Jefri Nur Arifin; Sutanto Sutanto (Ittishal Educational Research Journal, 2021)
Society and schools as the main agents of education must carry out innovations and creative methods in instructional processes in order to give their supports to the implementation of character education that has been launched by the Indonesian government through the Indonesian Ministry of Education. As an attempt to implement the character education in the instructional process, Sekolah Alam (nature-based school) Bengawan Solo (SABS) integrates the instructional process with environmental issues based on local wisdom. The curriculum developed by SABS has the holistic characteristics including: 1) character; 2) knowledge; 3) leadership; 4) entrepreneurship; and 5) an environmental insight. The instructional process in SABS has five main objectives: 1) fostering physical and mental health; 2) building a fighting spirit; 3) developing students’ critical thinking; 4) building perseverance; and 5) encouraging a simple life style. The social and cultural issues related to the Javanese and Islamic culture that take place in the community in the surrounding SABS are also taken into consideration by integrating themes related to the issues in the instructional process.